THE IX-XII CENTURIES RENAISSANCE SCIENTIFIC DISCOVERIES IN MATHEMATICS AND ASTRONOMY - Teshaboyeva Nafisa Zubaydulla qizi; Solnishkina Marina Ivanovna; Erkinova Muqaddas Olim qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: The Central Asian Renaissance, spanning from the 9th to the 12th centuries, represents a monumental era of intellectual awakening that transformed the cultural and scientific landscape of the medieval world. During this epoch, the cities of Bukhara, Samarkand, Khwarazm, and Fergana emerged as radiant centers of knowledge and civilization, where science, literature, philosophy, and theology flourished under the patronage of enlightened rulers and scholars. Distinguished polymaths such as Al-Khwarizmi, Al-Farghani, Al-Farabi, Al-Biruni, Ibn Sina, Al- Bukhari, and Omar Khayyam laid the foundational stones of modern mathematics, astronomy, medicine, and philosophy. Their groundbreaking discoveries, empirical methodologies, and philosophical rationalism not only advanced the frontiers of knowledge but also profoundly influenced the intellectual transformation of Europe during the later Renaissance. The Central Asian Renaissance thus stands as a vital bridge between the classical civilizations of antiquity and the modern scientific era, embodying humanity’s universal quest for truth, wisdom, and enlightenment.